Distribution of soil selenium and its relationship with parent rocks in Chengmai County, Hainan Island, China. (January 2022) - Gong, Jingjing; Yang, Jianzhou; Wu, Hui; Fu, Yangang; Gao, Jianwen; Tang, Shixin; Ma, Shengming
Abstract: Chengmai County of Hainan Island has plentiful Se-rich land resources. The distribution of Se-rich land is thought to be closely related to the geological background. However, the relationship between the Se enrichment in soil and the parent rocks remains unclear. The clarification of the relationship will be helpful for the development, management, and exploitation of Se-rich land. This paper studies the controlling effect of the composition and soil-forming process of parent rocks on Se enrichment. The results indicate that the Se content in metamorphic rocks (Se = 0.15–6.61 mg/kg) of the Tuolie Formation is significantly higher than that of other rocks, while there is a slight difference in the Se content between the granite (Se = 0.03–0.70 mg/kg) and basalt (Se = 0.05–0.77 mg/kg). The Se content in the overlying topsoil of different parent rocks is sorted as follows: Tuolie Formation (S1 t ) > basalt > granite > Quaternary loose accumulation. The comparison of the Se content in the rock and soil, the correlation of the Se-iodine content in the soil, and the mass balance calculation all imply that the enrichment of Se in the topsoil from the Tuolie Formation substrate is closely related to the high-Se content in the Tuolie Formation, while the Se content in the topsoil of basalt and granite substrate is more affected by the external input. The content of Se in the topsoil of basalt is higher than that of granite, which is attributed to its lower w (SiO2 ), higher w (TFe2 O3 ), w (Al2 O3 ), and organic matter content. The parent rock can indirectly influence the Se content in the overlying soil by altering the process and degree of soil formation. Highlights: The selenium in rocks and topsoil of Chengmai County, Hainan Province was studied. Se content in granite and basalt increases with the chemical weathering intensity. Se in topsoil overlying the Tuolie Formation was originated from the Se-rich rocks. The Se in the topsoil of basalt is higher than that of granite. Parent rock directly and indirectly influence the Se in the overlying soil.